Genome-wide analysis reveals MOF as a key regulator of dosage compensation and gene expression in Drosophila. - Kind, J.; Vaquerizas, J.M.; Gebhardt, P.; Gentzel, M.; Luscombe, N.M.; Bertone, P.; Akhtar, A. (Cell, 2008)
Dosage compensation, mediated by the MSL complex, regulates X-chromosomal gene expression in Drosophila. Here we report that the histone H4 lysine 16 (H4K16) specific histone acetyltransferase MOF displays differential binding behavior depending on whether the target gene is located on the X chromosome versus the autosomes. More specifically, on the male X chromosome, where MSL1 and MSL3 are preferentially associated with the 3' end of dosage compensated genes, MOF displays a bimodal distribution binding to promoters and the 3' ends of genes. In contrast, on MSL1/MSL3 independent X-linked genes and autosomal genes in males and females, MOF binds primarily to promoters. Binding of MOF to autosomes is functional, as H4K16 acetylation and the transcription levels of a number of genes are affected upon MOF depletion. Therefore, MOF is not only involved in the onset of dosage compensation, but also acts as a regulator of gene expression in the Drosophila genome.